Responsabilidade civil nos negócios eletrônicos firmados na região norte do Brasil - Galindo, Carlos Diniz (Universidade Federal do Tocantins, 2023)
With the increase in trade between countries, the world has undergone an accelerated technological evolution, which nowadays facilitates our daily lives, reflecting the change in standards of living. The objective of this work is to explore the civil liability in electronic business, particularly those signed in the northern region of the country. As for the specific objectives, it also aims to demonstrate how the ecommerce market has evolved in this same region and the application of the Civil Code with regard electronic business. The research method used was a bibliographic review, where the theme addressed will be exposed in an explanatory and descriptive manner, based on secondary data, in which an analysis of the entire contextual panorama was conducted through physical books or electronically available books and articles previously prepared and published in the electronic media such as monographs, various publications, theses, journalistic information, digital magazines and other sources available in the electronic media. It is possible to conclude that there is an evolution in the recent E-commerce business volume in the northern region, since the regulatory mark appeared, thus reaching the general objective of the work. In addition, the specific objectives were reached through the clear increase in the amount of business and sales generated by digital businesses. Potentiated by the Covid-19 pandemic, and by the convenience of home delivery of the product, in addition to the return and exchange guarantees provided by law, through the covered devices